Determinants of Riders’ Intention to Use Mobile Parking Applications: Evidence from Kathmandu Valley - Lacoul, Sanjana Shrestha; Kunwar, Ramesh; Basnet, Prashiddha; Adhikari, Kabita (NCC Journal, 2025)
Rapid urbanization and the increasing number of private vehicles have placed immense pressure on existing urban transport infrastructure, making efficient parking management a critical challenge for city authorities. Against a backdrop of acute urban parking scarcity and traffic congestion, this research aims to identify the key determinants of user acceptance of mobile parking application, the primary challenges hindering implementation, and viable managerial solutions to promote the successful deployment of smart parking technology. An explanatory research design was employed, grounded in an extended Technology Acceptance Model (TAM). Data were collected from 411 riders (drivers) across Kathmandu Valley using a structured questionnaire administered via digital and offline channels. The sample was selected using a non-probability convenience sampling technique. Both descriptive statistics and Structural Equation Modeling (SEM) with Partial Least Squares (PLS) were utilized to analyze the data. The results indicate that Perceived Usefulness, Parking App Attributes, Trust in the Parking App, and Social Influence have a significant positive impact on riders' intention to adopt mobile parking applications. Conversely, Perceived Ease of Use was found to have no significant direct effect on behavioral intention, although it positively influences Perceived Usefulness. The study also reveals a critical lack of awareness and trust among potential users, with only 24.09% aware of a previously launched application. Major implementation challenges identified include user distrust, inaccurate digital mapping data, and the absence of real-time tracking systems. Correspondingly, the most endorsed managerial solutions are robust promotional campaigns, precise location information for parking lots, and the integration of reliable online/offline payment systems. The study provides clear directives for application developers to prioritize data accuracy, real-time functionality, and security features. For policymakers and municipal authorities, it underscores the necessity of creating enabling regulations, ensuring data standardization, and acting as a trust anchor to facilitate successful public adoption.